# |
ODE |
Mathematica |
Maple |
\[
{}y y^{\prime \prime }+{y^{\prime }}^{3} = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right ) y^{\prime \prime } = y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = x {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = x {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = -{\mathrm e}^{-2 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = -{\mathrm e}^{-2 y}
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime } = \sin \left (2 y\right )
\] |
✗ |
✗ |
|
\[
{}2 y^{\prime \prime } = \sin \left (2 y\right )
\] |
✗ |
✗ |
|
\[
{}x^{3} y^{\prime \prime }-x^{2} y^{\prime } = -x^{2}+3
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = {\mathrm e}^{x} {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime } = {y^{\prime }}^{3} \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+{y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 1+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = \left (1+{y^{\prime }}^{2}\right )^{{3}/{2}}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime } = {y^{\prime }}^{2} \left (1-y^{\prime } \sin \left (y\right )-y y^{\prime } \cos \left (y\right )\right )
\] |
✓ |
✓ |
|
\[
{}\left (1+y^{2}\right ) y^{\prime \prime }+{y^{\prime }}^{3}+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (y y^{\prime \prime }+1+{y^{\prime }}^{2}\right )^{2} = \left (1+{y^{\prime }}^{2}\right )^{3}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime } = y^{\prime } \left (2 x -y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime } = y^{\prime } \left (3 x -2 y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime } = y^{\prime } \left (2-3 x y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}x^{4} y^{\prime \prime } = y^{\prime } \left (y^{\prime }+x^{3}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 2 x +\left (x^{2}-y^{\prime }\right )^{2}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime \prime }}^{2}-2 y^{\prime \prime }+{y^{\prime }}^{2}-2 x y^{\prime }+x^{2} = 0
\] |
✗ |
✓ |
|
\[
{}{y^{\prime \prime }}^{2}-x y^{\prime \prime }+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime \prime }}^{3} = 12 y^{\prime } \left (x y^{\prime \prime }-2 y^{\prime }\right )
\] |
✗ |
✓ |
|
\[
{}3 y y^{\prime } y^{\prime \prime } = {y^{\prime }}^{3}-1
\] |
✓ |
✓ |
|
\[
{}4 y {y^{\prime }}^{2} y^{\prime \prime } = {y^{\prime }}^{4}+3
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = -\cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+9 y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+2 y = 12 x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+2 y = x^{2}+2 x +1
\] |
✓ |
✓ |
|
\[
{}x^{3} {y^{\prime }}^{2}+x^{2} y y^{\prime }+4 = 0
\] |
✓ |
✓ |
|
\[
{}6 x {y^{\prime }}^{2}-\left (2 y+3 x \right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}9 {y^{\prime }}^{2}+3 y^{4} y^{\prime } x +y^{5} = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{3} {y^{\prime }}^{2}-4 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{6} {y^{\prime }}^{2}-2 x y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}5 {y^{\prime }}^{2}+6 x y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} {y^{\prime }}^{2}-y \left (1+x \right ) y^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{5} {y^{\prime }}^{2}+12 x^{4} y y^{\prime }+9 = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{2} {y^{\prime }}^{3}-2 x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{4}+x y^{\prime }-3 y = 0
\] |
✗ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{3}-2 x y {y^{\prime }}^{2}+y^{\prime } y^{2}+1 = 0
\] |
✓ |
✓ |
|
\[
{}16 x {y^{\prime }}^{2}+8 y y^{\prime }+y^{6} = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-\left (x^{2}+1\right ) y^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}-2 x y^{\prime }-y = 0
\] |
✗ |
✓ |
|
\[
{}9 x y^{4} {y^{\prime }}^{2}-3 y^{5} y^{\prime }-1 = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}-\left (1+2 x y\right ) y^{\prime }+y^{2}+1 = 0
\] |
✓ |
✓ |
|
\[
{}x^{6} {y^{\prime }}^{2} = 16 y+8 x y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2} = \left (x -y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}\left (y^{\prime }+1\right )^{2} \left (-x y^{\prime }+y\right ) = 1
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}-{y^{\prime }}^{2}+x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}+y \left (1-x \right ) y^{\prime }-y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y {y^{\prime }}^{2}-\left (x +y\right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}+\left (k -x -y\right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{3}-2 y {y^{\prime }}^{2}+4 x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 x y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (4 x^{2}+1\right ) y^{\prime \prime }-8 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-4 x^{2}+1\right ) y^{\prime \prime }+8 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }-4 x y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime \prime }+10 x y^{\prime }+20 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+4\right ) y^{\prime \prime }+2 x y^{\prime }-12 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-9\right ) y^{\prime \prime }+3 x y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 x y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+4\right ) y^{\prime \prime }+6 x y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 x^{2}+1\right ) y^{\prime \prime }-5 x y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x^{2} y = 0
\] |
✓ |
✓ |
|
\[
{}\left (-4 x^{2}+1\right ) y^{\prime \prime }+6 x y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 x^{2}+1\right ) y^{\prime \prime }+3 x y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+x^{2} y^{\prime \prime }+5 x y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+x y^{\prime }+3 y = x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 x y^{\prime }+7 y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }+9 x y^{\prime }-36 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+4\right ) y^{\prime \prime }+x y^{\prime }-9 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+4\right ) y^{\prime \prime }+3 x y^{\prime }-8 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (9 x^{2}+1\right ) y^{\prime \prime }-18 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (3 x^{2}+1\right ) y^{\prime \prime }+13 x y^{\prime }+7 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 x^{2}+1\right ) y^{\prime \prime }+11 x y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 \left (x +3\right ) y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\left (x -2\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-2 x +2\right ) y^{\prime \prime }-4 \left (x -1\right ) y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}2 x \left (1+x \right ) y^{\prime \prime }+3 \left (1+x \right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }+4 x y^{\prime }+\left (4 x^{2}-1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }+4 x y^{\prime }-\left (4 x^{2}+1\right ) y = 0
\] |
✓ |
✓ |
|
\[
{}4 x y^{\prime \prime }+3 y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} \left (1-x \right ) y^{\prime \prime }-x \left (1+7 x \right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime \prime }+5 \left (1-2 x \right ) y^{\prime }-5 y = 0
\] |
✓ |
✓ |
|
\[
{}8 x^{2} y^{\prime \prime }+10 x y^{\prime }-\left (1+x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime \prime }+\left (2-x \right ) y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}2 x \left (x +3\right ) y^{\prime \prime }-3 \left (1+x \right ) y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime \prime }+\left (-2 x^{2}+1\right ) y^{\prime }-4 x y = 0
\] |
✓ |
✓ |
|
\[
{}x \left (4-x \right ) y^{\prime \prime }+\left (2-x \right ) y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} y^{\prime \prime }+x y^{\prime }-\left (1+x \right ) y = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime \prime }+\left (2 x +1\right ) y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime \prime }+\left (2 x +1\right ) y^{\prime }-5 y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }-3 x \left (1-x \right ) y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }+x \left (4 x -1\right ) y^{\prime }+2 \left (3 x -1\right ) y = 0
\] |
✓ |
✓ |
|